Pharmacists' confidence in explaining biosimilars to patients before a nationwide medicine change: A cross-sectional study - Chiara Gasteiger; Norina Gasteiger; Keith J. Petrie (Elsevier, 2022)
Background: Biosimilars can improve patient access to biological medicines. Although biosimilars have been shown to be equally effective and safe, some patients remain reluctant to transition to biosimilars. Pharmacists may support patients changing to biosimilars and are often at the frontline for dealing with queries and concerns, but their confidence and readiness for this role are unclear. Objective: This study examines pharmacists' confidence in explaining biosimilars to patients and explores the information they would provide in response to common queries. Methods: Practicing community, hospital, and primary care pharmacists (N = 142) in New Zealand completed an Internet-based survey on their experience and familiarity with bio-originators and biosimilars, attitudes and concerns towards biosimilars, confidence in explaining key concepts, and responses to common queries. A hierarchical linear regression was conducted to examine possible factors associated with confidence in explaining biosimilars, and a content synthesis was conducted to examine responses to common patient queries. Results: Pharmacists were most confident in explaining how biosimilars are administered, their efficacy, and cost-saving, and least confident in describing manufacturing and testing. Respondents who had more positive attitudes (B = 1.64, p < .001) and more familiarity with biosimilars (B = 27.15, p < .001) were more confident in educating patients. Pharmacists' main concerns about biosimilars included reduced efficacy, safety, and a lack of knowledge and acceptance. Responses to common queries were diverse but further highlighted several gaps in knowledge. Gaps included being unable to define biosimilars, provide information on side effects, and believing that biosimilars undergo the same testing process as bio-originators. Pharmacists wanted resources (written and Internet-based) to improve their knowledge and ability to educate patients. Conclusions: Pharmacists reported a lack of knowledge and confidence in explaining manufacturing processes and testing of biosimilars. Additional resources are needed to support their practice and may help improve patient and companion acceptance of biosimilars.